Graphene-based THz wave gas sensor for methanol detection - Saber Norouzi; Hosein Alavi-Rad; Seyed Saleh Ghoreishi Amiri; Reza Yousefi; Hadi Dehbovid (Sensing and Bio-Sensing Research)
Context: This study aims to model and simulate a graphene-based Methanol (CH3OH) detector. The primary objective of this research is to obtain different absorption responses against different methanol concentrations in the surrounding environment. This paper proposes a gap between layers to intensify the direct interaction between methanol molecules and the detector. Furthermore, the THz spectrum is considered due to its potential and graphene-reliable modeling in THz frequencies. We investigate the effects of parameter variations and consequent response deviations. The significance of this research lies in that the detector is sensitive to the surrounding environment's refractive index. This sensitivity can be leveraged to detect any target components in air or liquid. Methods: This study was conducted involving an equivalent circuit model plus full-wave numerical simulation. Data were collected from MATLAB and CST, and they show acceptable convergence. The design methodology includes investigating impedance matching between the detector and the surrounding environment. The findings indicate that the proposed graphene-based detector appropriately reacts against methanol concentration. Our results demonstrate significant deviations in absorption response for methanol concentration above 50 ppm while the absorption response is highly robust against geometrical variations. It is shown that methanol vapor with concentrations from 50 ppm to 500 ppm covers absorption peaks all over the THz spectrum. Such a reliable methanol detector is highly in demand for healthcare applications due to its efficiency and capabilities.